Method for manufacturing a proton-conducting membrane
Patent Information
- Application Number
- CN202280043857.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-22
- Filing Date
- 2022-06-13
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-06-13
AI Technical Summary
[0020]本公开中,在通过加压成形使聚磷酸中溶解的电解质树脂材料薄膜化时,作为与电解质树脂材料接触的树脂薄膜,使用具有酸性取代基的树脂薄膜。因此,空气中的水分能够经由树脂薄膜到达电解质树脂材料中,通过促进聚磷酸的水解而能够使其磷酸化,从而能够容易从质子传导膜上剥离树脂薄膜。由此,即使在通过加压成形由聚磷酸中溶解的电解质树脂材料制造质子传导膜的情况下,也能够得到平坦性及致密性高的质子传导膜,能够得到高品质的质子传导膜。
Smart Images

Figure CN117546323B_ABST
Abstract
Description
[0001] Cross-referencing of related applications
[0002] This application claims priority based on Japanese Patent Application No. 2021-103216, filed on June 22, 2021, the contents of which are incorporated herein by reference. Technical Field
[0003] This disclosure relates to a method for manufacturing a proton-conducting membrane. Background Technology
[0004] Currently, from the perspective of reducing the cost and simplifying the system of solid polymer fuel cell systems, there is a growing expectation for humidification-free, mid-temperature operating fuel cells that can operate at temperatures above 100°C and under humidification-free conditions. The proton exchange membrane plays a crucial role in enabling fuel cells to operate without humidification.
[0005] In non-patent literature 1-4, a polymer membrane consisting of polybenzimidazole (PBI) doped with phosphoric acid as a proton carrier was proposed as a proton conduction membrane for a non-humidified, medium-temperature fuel cell. The membrane resistance of the phosphoric acid-doped polymer membrane is inversely proportional to the amount of phosphoric acid doped; the greater the amount of phosphoric acid, the lower the membrane resistance.
[0006] Non-patent documents 5 and 6 propose a method (PPA process: wet phosphoric acid purification process) that involves dissolving an electrolyte resin material in polyphosphoric acid and forming a thin film. The resulting polymer film is then exposed to atmospheric humidity, where the moisture in the atmosphere hydrolyzes and phosphorylates the polyphosphoric acid, resulting in a phosphoric acid-doped polymer film. It is generally known that the PPA process, compared to methods that obtain phosphoric acid-doped polymer films by immersing the polymer film in phosphoric acid, allows for the doping of more phosphoric acid and reduces film resistance.
[0007] Existing technical documents
[0008] Non-patent literature
[0009] Non-patent literature 1: Quartarone, E.; Mustarelli, P. Polymer fuel cells based on polybenzimidazole / H3PO4. Energy Environ. Sci. 2012, 5, 6436-6444.
[0010] Non-patent document 2: Samms, SR; Wasmus, S.; Savinell, RF Thermal stability of proton conducting acid doped polybenzimidazole in simulated fuel cell environments. J. Electrochem. Soc. 1996, 143, 1225-1232.
[0011] Non-patent document 3: Weng, D.; Wainright, JS; Landau, U.; Savinell, RFElectro-osmotic drag coefficient of water and methanol in polymer electrolytes atelevated temperatures. J. Electrochem. Soc. 1996, 143, 1260-1263.
[0012] Non-Patent Literature 4: Wang, J.-T.; Savinell, RF; Wainright, J.; Litt, M.; Yu, H. AH2 / O2 fuel cell using acid-doped polybenzimidazole as polymerelectrolyte. Electrochim. Acta 1996, 41, 193-197.
[0013] Non-patent literature 5: XIAO, Lixiang, et al. High-temperature polybenzimidazole fuel cell membranes via a sol-gel process. Chemistry of Materials, 2005, 17.21: 5328-5333.
[0014] Non-patent literature 6: SEEL, DC, et al. High-temperature polybenzimidazole-based membranes. Handbook of fuel cells, 2010. Summary of the Invention
[0015] The polyphosphoric acid used in the PPA process has high adhesion. Therefore, in manufacturing methods that involve pressurizing the electrolyte resin material dissolved in polyphosphoric acid, the polymer membrane adheres to protective sheets or jigs used in the pressurization process, making peeling difficult and hindering the production of films with high flatness and density. Consequently, in manufacturing methods that involve pressurizing the electrolyte resin material dissolved in polyphosphoric acid, the quality of the proton conduction membrane is reduced, leading to a decline in the quality of the fuel cell.
[0016] Because polyphosphoric acid loses its adhesive properties upon hydrolysis, it becomes readily hydrolyzed in manufacturing methods where one side of the polymer film can be exposed to the atmosphere, such as drop casting, blade coating, and spin coating. This allows the polymer film to be easily peeled off from protective sheets. However, these manufacturing methods suffer from poor productivity, making large-area and mass production of polymer films difficult.
[0017] In view of the above-mentioned problems, the present disclosure aims to improve the quality of the proton conduction membrane in a method for manufacturing a proton conduction membrane by pressurizing and thinning an electrolyte resin material dissolved in polyphosphoric acid.
[0018] To achieve the above objectives, the present disclosure employs the following technical means.
[0019] This disclosure relates to a method for manufacturing a proton-conducting membrane comprising a pressurization step, a hydrolysis step, and a stripping step. In the pressurization step, an electrolyte resin material is formed into a film by contacting at least one surface of an electrolyte resin material dissolved in polyphosphoric acid with the film and applying pressure. In the hydrolysis step, the polyphosphoric acid is phosphorylated by hydrolysis after the pressurization step. In the stripping step, the resin film is peeled off from the film-like electrolyte resin material after the hydrolysis step, resulting in a proton-conducting membrane formed from a film-like electrolyte resin material containing phosphoric acid. The resin constituting the resin film has acidic substituents.
[0020] In this disclosure, when the electrolyte resin material dissolved in polyphosphoric acid is thin-filmed by pressure molding, a resin film with acidic substituents is used as the resin film in contact with the electrolyte resin material. Therefore, moisture in the air can reach the electrolyte resin material through the resin film, promoting the hydrolysis of polyphosphoric acid and causing it to phosphorylate, thereby facilitating the peeling of the resin film from the proton conduction membrane. Thus, even when a proton conduction membrane is manufactured from an electrolyte resin material dissolved in polyphosphoric acid by pressure molding, a proton conduction membrane with high flatness and density can be obtained, resulting in a high-quality proton conduction membrane. Attached Figure Description
[0021] Figure 1 This is a conceptual diagram of a fuel cell according to an embodiment of the present disclosure.
[0022] Figure 2This is a diagram illustrating the manufacturing process of a proton-conductive film formed by compression molding.
[0023] Figure 3 This is a diagram illustrating the phosphorylation of polyphosphoric acid during the hydrolysis process.
[0024] Figure 4 This is a diagram illustrating the manufacturing process of a proton-conductive film formed by roll forming.
[0025] Figure 5 These are diagrams illustrating the electrolyte materials, protective sheets, and molding methods of the embodiments and comparative examples.
[0026] Figure 6 These are graphs showing various measured values for the examples and comparative examples. Detailed Implementation
[0027] Hereinafter, one embodiment of the present disclosure will be described with reference to the accompanying drawings.
[0028] like Figure 1 As shown, the fuel cell unit 100 includes a cathode 110, an anode 120, and an electrolyte membrane 130. Alternatively, the cathode 110 can be referred to as the air electrode, and the anode 120 as the hydrogen electrode.
[0029] The fuel cell unit 100 outputs electrical energy through an electrochemical reaction between fuel gas (hydrogen) and oxidant gas (oxygen from the air). Using the fuel cell unit 100 as the basic unit, it can be used in a multi-layered stacked structure.
[0030] If reactive gases such as hydrogen and air are supplied to the fuel cell unit 100, then as shown below, hydrogen and oxygen undergo an electrochemical reaction to output electrical energy.
[0031] (Anode side) H2→2H + +2e -
[0032] (Cathode side) 2H + +1 / 2O2+2e - →H2O
[0033] At this point, in anode 120, hydrogen is ionized into electrons (e) through a catalytic reaction. - ) and proton (H + ), proton (H + Protons (H+) move along the electrolyte membrane 130. Meanwhile, in the cathode 110, protons (H+) moving from the anode 120 side... + Electrons flowing from the outside and oxygen (O2) in the air react to produce water.
[0034] The fuel cell unit 100 of this embodiment generates electricity at a temperature of 100°C or higher and without humidifying the electrolyte membrane 130. In other words, dry air can be supplied to the cathode 110 during the operation of the fuel cell unit 100.
[0035] The cathode 110 is composed of a cathode-side catalyst layer 111 that is tightly disposed on the surface of the electrolyte membrane 130 on the air electrode side and a cathode-side diffusion layer 112 disposed on the outside of the cathode-side catalyst layer 111.
[0036] The anode 120 is composed of an anode-side catalyst layer 121 that is tightly disposed on the surface of the electrolyte membrane 130 on the hydrogen electrode side and an anode-side diffusion layer 122 disposed on the outside of the anode-side catalyst layer 121.
[0037] Each catalyst layer 111 and 121 is formed by carbon-supported platinum catalysts, etc., on a carbon support for supporting catalysts (such as platinum) to promote electrochemical reactions, and each diffusion layer 112 and 122 is formed by carbon interweaving, etc.
[0038] Electrolyte membrane 130 is a proton-conducting membrane. In this embodiment, a polymer membrane doped with phosphoric acid is used as the proton-conducting membrane. Phosphoric acid is a proton-conducting substance. The polymer membrane doped with phosphoric acid is also referred to as a phosphoric acid-doped polymer membrane.
[0039] In this embodiment, the polyphosphoric acid solution of the electrolyte resin material is thinned by pressure molding, and the polyphosphoric acid contained in the obtained polymer film is phosphorylated by hydrolysis, thereby obtaining a phosphoric acid doped polymer film, i.e., a proton conduction film.
[0040] In this embodiment, the thickness of the proton-conducting membrane is set to 150 μm or less. By setting the thickness of the proton-conducting membrane to 150 μm or less, the membrane resistance can be reduced and the proton conductivity improved. Furthermore, in this embodiment, the thickness of the proton-conducting membrane is set to 1 μm or more. By setting the thickness of the proton-conducting membrane to 1 μm or more, the strength of the proton-conducting membrane can be ensured.
[0041] In this embodiment, the concentration of the electrolyte resin material in the polyphosphoric acid solution is set within the range of 1 wt% to 20 wt%. If the concentration of the electrolyte resin material is below 1 wt%, film formation becomes difficult. If the concentration of the electrolyte resin material is above 20 wt%, a high-quality polymer film cannot be obtained during film formation.
[0042] The electrolyte resin material constituting the proton-conducting membrane is preferably a polymer that readily retains phosphoric acid. As a polymer readily retaining phosphoric acid, basic resin materials having N or NH in the main chain or side chain, or resin materials having at least one acidic substituent selected from sulfonyl (-SO3H), carboxyl (-COOH), hydroxyl (-OH), phosphine (-PO(OH)2), and their derivatives, can be used. A derivative is a substance obtained by replacing a portion of its chemical structure with other atoms or groups.
[0043] As an electrolyte resin material constituting the proton conduction membrane, at least one selected from polybenzimidazole, sulfonated polyimide, perfluorosulfonic acid polymer and their derivatives can be used.
[0044] As electrolyte resin materials constituting the proton-conducting membrane, phosphoric acid-doped QAPOH or PWN70 can be used, as shown below. Phosphoric acid-doped QAPOH is disclosed in "K.-S. Lee, JSSpendelow, Y.-K. Choe, C. Fujimoto, YSKim, Nature Energy 2016, 1.", and PWN70 is disclosed in "V. Atanasov, A.S. Lee, EJPark, S. Maurya, EDBaca, C. Fujimoto, M. Hibbs, I. Matanovic, J. Kerres, YSKim, Nature Materials 2020".
[0045] [Chemical Formula 1]
[0046]
[0047] [Chemical Formula 2]
[0048]
[0049] Next, the method for manufacturing the proton-conducting membrane according to this embodiment will be described. As described above, in this embodiment, the proton-conducting membrane is thinned by press molding an electrolyte resin material dissolved in polyphosphoric acid. For example, compression molding and roll forming can be used for press molding.
[0050] The method for manufacturing the proton-conducting membrane according to this embodiment includes at least a pressurization step, a hydrolysis step, and a stripping step. These steps are performed in the order of pressurization, hydrolysis, and stripping.
[0051] In the pressurization process, two protective sheets are brought into contact with the electrolyte resin material dissolved in polyphosphoric acid from both sides, and pressure is applied and calendered in this state to obtain a polymer film. In the hydrolysis process, the polyphosphoric acid contained in the polymer film is phosphorylated by hydrolysis. In the peeling process, the protective sheets are peeled off from the polymer film. Through the above processes, a proton-conducting membrane formed by the phosphoric acid-doped polymer film can be obtained.
[0052] The protective sheet is used between the electrolyte resin material dissolved in polyphosphoric acid and the pressurizing device, serving as a base when calendering the electrolyte resin material. In this embodiment, a resin film with acidic substituents is used as the protective sheet. The resin film with acidic substituents is also referred to as an acidic resin film. The acidic resin film readily absorbs moisture from the air, and moisture easily permeates through it.
[0053] As a resin material constituting an acidic resin film, a resin material having at least one acidic substituent selected from sulfonyl (-SO3H), carboxyl (-COOH), hydroxyl (-OH), phosphinyl (-PO(OH)2), and their derivatives can be used. Examples of acidic resin films include perfluorosulfonic acid polymers such as Nafion (a registered trademark of DuPont), poly(vinylphosphonic acid), and polystyrene sulfite.
[0054] Here, we adopt Figure 2 The manufacturing method of the proton-conducting membrane using compression molding is described. For example... Figure 2 As shown, the pressing and forming apparatus 10 includes an upper pressing plate 11 and a lower pressing plate 12. The pressing and forming apparatus 10 is a uniaxial press that applies pressure using the upper pressing plate 11. During pressing and forming, two protective sheets 200 and 201 are used.
[0055] In the material supply process, an electrolyte resin material 202 dissolved in polyphosphoric acid is supplied between the first protective sheet 200 and the second protective sheet 201. The electrolyte resin material 202 is a polyphosphoric acid solution, which is a high-viscosity liquid. The electrolyte resin material 202 is sandwiched between the first protective sheet 200 and the second protective sheet 201.
[0056] During the pressurization process, the first protective sheet 200 and the second protective sheet 201 are pressurized from the outside by the upper pressing plate 11 and the lower pressing plate 12. As a result, the electrolyte resin material 202 sandwiched between the first protective sheet 200 and the second protective sheet 201 is calendered into a thin film.
[0057] In the pressurization process, to facilitate thin-film formation, it is preferable to maintain the electrolyte resin material 202 in a high-viscosity liquid state, and hydrolysis of the polyphosphoric acid contained in the electrolyte resin material 202 is preferably not performed. Therefore, the ambient humidity is lower in the pressurization process compared to the hydrolysis process. Ambient humidity refers to the humidity around the electrolyte resin material 202. Specifically, in the pressurization process, it is preferable to set the ambient humidity to a relative humidity below 15%. The ambient humidity can be adjusted using a humidity adjustment device (not shown). The humidity adjustment device is a device capable of humidifying and dehumidifying.
[0058] In the hydrolysis process, the electrolyte resin material 202, sandwiched between two protective sheets 200 and 201, is removed from the upper pressing plate 11 and the lower pressing plate 12 and exposed to air with a specified humidity for a specified time. In the hydrolysis process, the electrolyte resin material 202 sandwiched between the two protective sheets 200 and 201 only needs to be left for a few minutes.
[0059] In the hydrolysis process, higher ambient humidity is preferable to promote the hydrolysis of polyphosphoric acid contained in the electrolyte resin material 202. The ambient humidity is increased in the hydrolysis process compared to the pressurization process. Preferably, the ambient humidity in the hydrolysis process is set to a relative humidity of 15% or higher.
[0060] In this embodiment, an acidic resin film is used as the protective sheets 200 and 201. Therefore, during the hydrolysis process, moisture in the air is supplied to the electrolyte resin material 202 through the protective sheets 200 and 201.
[0061] like Figure 3 As shown, in the hydrolysis process, the polyphosphoric acid contained in the electrolyte resin material 202 is phosphorylated by hydrolysis.
[0062] Return to Figure 2 In the peeling process, the first protective sheet 200 and the second protective sheet 201 are peeled off from the membrane-like electrolyte resin material 202. The electrolyte resin material 202 loses its adhesiveness due to the hydrolysis of polyphosphoric acid, making it easy to peel off the protective sheets 200 and 201. Thus, a proton-conducting membrane formed from the membrane-like electrolyte resin material 202 containing phosphoric acid can be obtained. Since residual phosphoric acid and water adhere to the proton-conducting membrane, they need to be removed by wiping.
[0063] The protective sheets 200 and 201 removed during the stripping process can be returned to the previous process, namely the material supply process and the pressurization process, and can be reused in the next manufacturing of the proton conduction membrane. In other words, the protective sheets 200 and 201 can be reused.
[0064] Next, adopt Figure 4 The manufacturing method of a proton-conducting membrane using roll forming is described.
[0065] like Figure 4 As shown, the roll forming device 20 includes an extruder 21, pressure rolls 22 and 23, and take-up rolls 24 and 25.
[0066] In the material supply and pressurization processes, electrolyte resin material 202 dissolved in polyphosphoric acid is supplied from the extruder 21 between the first protective sheet 200 and the second protective sheet 201. Further, pressure is applied to the first protective sheet 200 and the second protective sheet 201 from the outside via the upper pressure roller 22 and the lower pressure roller 23. As a result, the electrolyte resin material 202 is calendered into a thin film.
[0067] In the hydrolysis process, the electrolyte resin material 202, sandwiched between two protective sheets 200 and 201, is exposed to air with a specified humidity for a specified time. In the hydrolysis process, simply stopping the pressure rollers 22 and 23 and the take-up rollers 24 and 25 and allowing the electrolyte resin material 202 sandwiched between the protective sheets 200 and 201 to stand for a few minutes is sufficient.
[0068] Even in roll forming, in the pressurization process, the ambient humidity is reduced to suppress the hydrolysis of polyphosphoric acid contained in the electrolyte resin material 202, and in the hydrolysis process, the ambient humidity is increased compared to the pressurization process to promote the hydrolysis of polyphosphoric acid. It is preferable to set the ambient humidity in the pressurization process to a relative humidity of less than 15%, and it is preferable to set the ambient humidity in the hydrolysis process to a relative humidity of 15% or more.
[0069] During the hydrolysis process, moisture from the air can be supplied to the electrolyte resin material 202 through protective sheets 200 and 201. As a result, the polyphosphoric acid contained in the electrolyte resin material 202 undergoes hydrolysis and phosphorylation.
[0070] In the peeling process, the first protective sheet 200 and the second protective sheet 201 are peeled off from the membrane-like electrolyte resin material 202. Figure 4 The peeling process shown illustrates the state where the second protective sheet 201 has been peeled off from the electrolyte resin material 202, and the state where the first protective sheet 200 has been peeled off from the electrolyte resin material 202. The upper protective sheet 200 is wound onto the first take-up roller 24, and the film-like electrolyte resin material 202 is wound onto the second take-up roller 25. The electrolyte resin material 202 loses its adhesiveness due to the hydrolysis of polyphosphoric acid, thus making it easy to peel off the protective sheets 200 and 201.
[0071] Thus, a proton-conducting membrane formed from a membrane-like electrolyte resin material 202 containing phosphoric acid can be obtained. Since residual phosphoric acid and water adhere to the proton-conducting membrane, they need to be removed from the electrolyte resin material 202 by wiping.
[0072] Even during roll forming, the protective sheets 200 and 201 that are peeled off in the peeling process can be returned to the previous process, namely the material supply process and the pressurization process, and can be reused in the next manufacturing of the proton conduction membrane.
[0073] Next, adopt Figure 5 , Figure 6 Examples 1-8 and Comparative Examples 1-8 will be described. Figure 5 As shown, the electrolyte resin material, protective sheet, and molding method differ in Examples 1-8 and Comparative Examples 1-8.
[0074] In Examples 1, 3, 5, 7 and Comparative Examples 1, 3, 5, 7, mp-polybenzimidazole (mp-PBI), as shown below, was used as the electrolyte resin material. mp-PBI is disclosed in "Appl. Energy Mater. 2019, 2, 1720-1726".
[0075] [Chemical Formula 3]
[0076]
[0077] In Examples 2, 4, 6, 8 and Comparative Examples 2, 4, 6, 8, AB-polybenzimidazole (AB-PBI), as shown below, was used as the electrolyte resin material. AB-PBI is disclosed in "J. Polym. Sci., A, Chem. 2012, 50, 306-313".
[0078] [Chemical Formula 4]
[0079]
[0080] Here, the method for synthesizing mp-PBI polyphosphoric acid solution is described.
[0081] [Chemical Formula 5]
[0082]
[0083] In a 500 ml separating flask, 36.4 g (170.00 mmol) of 3,3'-diaminobenzidine, 24.7 g (148.75 mmol) of isophthalic acid, 3.5 g (21.25 mmol) of terephthalic acid, and 595 g of polyphosphoric acid were added sequentially. The separating flask containing these materials was immersed in an oil bath preheated to 60°C and stirred under an argon flow using a mechanical stirrer equipped with magnetically coupled stir plates.
[0084] The mixture was heated and stirred according to the specified heating conditions, ultimately reaching 195°C and stirring for 12 hours. The heating and stirring conditions were as follows: starting from 60°C, the temperature was increased by 20°C every 15 minutes, maintained at 140°C for 2 hours, then increased by 55°C every 30 minutes, and maintained at 195°C for 12 hours. After reaching 195°C, stirring was stopped for 2 hours, and the reaction continued as is. After heating and stirring were completed, the reaction mixture was cooled to 100°C (bath temperature) to obtain 601.1 g of mp-PBI polyphosphoric acid solution.
[0085] Next, the synthesis method of the polyphosphoric acid solution of AB-PBI will be described. First, the synthesis method of the intermediate 2,2'-bibenzimidazole-5,5'-dicarboxylic acid (BBCDA) will be described.
[0086] [Chemical Formula 6]
[0087]
[0088] In a 3L four-necked flask, 65.6 g (431.15 mmol) of 3,4-diaminobenzoic acid and 1640 ml of dehydrated methanol were added under an argon atmosphere and the flask was chilled. Then, 38 g (215.58 mmol) of methyl 2,2,2-trichloroacetyliminoate was added dropwise to the flask. After the addition was complete, the flask was heated to 50°C (internal temperature) and stirred for 24 hours.
[0089] After the reaction solution was cooled, the crystals were separated into solid and liquid phases by centrifugation. The centrifugation was carried out at 10°C and 3100 rpm for 15 minutes.
[0090] After washing the solid fraction three times with methanol and once with ethanol, it was dried under reduced pressure overnight at 100°C to obtain 37.2 g of crude product. 1.3 L of dimethyl sulfoxide (DMSO) was added to the crude product and the mixture was heated to dissolve it. Hot water was then added until the mixture became slightly turbid, after which it was cooled to ice.
[0091] One hour later, solid-liquid separation was performed by centrifugation. Centrifugation was carried out at 5°C and 3100 rpm for 15 minutes.
[0092] After washing the solid fraction twice with ethanol, it was dried under reduced pressure overnight at 220°C to obtain 32.7 g of yellow powder. The yield was 47.1%. Thus, the intermediate BBCDA was obtained.
[0093] Continuing, the method for synthesizing polyphosphoric acid solution using BBCDA's AB-PBI will be described.
[0094] [Chemical Formula 7]
[0095]
[0096] 3,3'-diaminobenzidine, BBDCA, and polyphosphoric acid were added sequentially to a 500 ml separating flask. The separating flask containing these materials was then immersed in an oil bath preheated to 60°C and stirred under an argon flow using a mechanical stirrer equipped with magnetically coupled stir plates.
[0097] The mixture was heated and stirred according to the specified heating conditions, ultimately reaching 220°C and stirring for 20 hours. The heating and stirring conditions were as follows: starting from 60°C, the temperature was increased by 20°C every 15 minutes, maintained at 140°C for 2 hours, then increased by 40°C every 30 minutes, maintained at 180°C for 10 hours. Then, the temperature was increased by 40°C every 30 minutes, maintained at 220°C for 20 hours. After heating and stirring, the reaction mixture was cooled to 120°C (bath temperature) to obtain 587.1 g of AB-PBI polyphosphoric acid solution.
[0098] In Examples 1 and 2, Nafion 117 was used as a protective sheet, and a proton-conducting membrane was obtained by compression molding. In Examples 3 and 4, poly(vinylphosphonic acid) was used as a protective sheet, and a proton-conducting membrane was obtained by compression molding. In Examples 5 and 6, Nafion 117 was used as a protective sheet, and a proton-conducting membrane was obtained by roll forming. In Examples 7, Nafion 117 from Example 1 was used for reuse, and in Example 8, Nafion 117 from Example 2 was used for reuse.
[0099] In Comparative Examples 1 and 2, polyethylene terephthalate was used as the protective sheet, and the proton-conducting membrane was obtained by compression molding. In Comparative Examples 3 and 4, polybenzimidazole was used as the protective sheet, and the proton-conducting membrane was obtained by compression molding. In Comparative Examples 5 and 6, polyimide was used as the protective sheet, and the proton-conducting membrane was obtained by compression molding. In Comparative Examples 7 and 8, porous polytetrafluoroethylene was used as the protective sheet, and the proton-conducting membrane was obtained by compression molding.
[0100] The protective films of Comparative Examples 1 to 8 are non-acidic resin films without acidic substituents. The protective films of Comparative Examples 7 and 8 are porous materials.
[0101] In the compression molding of Examples 1-4, 7, 8 and Comparative Examples 1-8, 0.2 g of electrolyte resin material was sandwiched between protective sheets and pressurized at room temperature with a pressure of 10 kN for 60 seconds, 30 kN for 10 seconds, 50 kN for 10 seconds, and 75 kN for 10 seconds. Then, it was left to stand for 1 minute for hydrolysis to obtain a proton-conducting membrane sandwiched between two protective sheets.
[0102] In the roll forming of Examples 5 and 6, 0.2 grams of electrolyte resin material was sandwiched between protective sheets and passed twice through a roller with a gap of 200 μm, thus applying pressure. Then, it was left to stand for 1 minute for hydrolysis to obtain a proton-conducting membrane sandwiched between two protective sheets.
[0103] Peel strength, film thickness, surface roughness, phosphoric acid content, and film resistance were measured on the proton-conducting membranes obtained in Examples 1-8 and Comparative Examples 1-8. The various measured values of Examples 1-8 and Comparative Examples 1-8 are as follows: Figure 6 As shown in the image.
[0104] For peel strength testing, a 90° peel strength test fixture P90-200N and a force gauge DRP-50N manufactured by IMADA Corporation were used to measure the 90° peel strength when peeling the protective sheet from the proton conduction membrane. The proton conduction membrane, sandwiched between two protective sheets, was cut into rectangles of 20mm × 50mm for peel strength testing. One protective sheet was fixed to a stainless steel base, and the short side of the other protective sheet was clamped using the clamps provided with the force gauge. The sheet was pulled linearly at a 90° angle at a speed of 10mm / min, and the force (N) required for peeling was measured.
[0105] In Examples 1-8, the peel strength was 0.13-0.53 N, allowing the protective sheet to be easily peeled off from the proton-conducting membrane. In Examples 1-8, it is believed that moisture in the air reaches the proton-conducting membrane via the protective sheet formed from the acidic resin film, undergoing hydrolysis of polyphosphoric acid, thereby reducing the adhesion. In Examples 1-8, proton-conducting membranes with high flatness and density were obtained.
[0106] In Comparative Examples 1-6, the peel strength was 2.47-3.87 N, which was significantly increased compared to Examples 1-8. In Comparative Examples 1-6, it was believed that moisture in the air did not reach the proton-conducting membrane through the protective sheet formed by the non-acidic resin film, and hydrolysis of polyphosphoric acid did not occur; therefore, the adhesion was not reduced. In Comparative Examples 1-6, if the protective sheet was peeled off, the proton-conducting membrane was severely damaged, and a proton-conducting membrane with high flatness and density could not be obtained.
[0107] In Comparative Examples 7 and 8, the peel strength was 1.58–1.87 N, which was higher than that of Examples 1–8 but lower than that of Comparative Examples 1–6. In Comparative Examples 7 and 8, it was believed that moisture in the air reached the proton-conducting membrane through the protective sheet formed by the porous material, and underwent hydrolysis of polyphosphoric acid, resulting in a slight decrease in adhesion. In Comparative Examples 7 and 8, if the protective sheet was peeled off, the proton-conducting membrane was severely damaged, and a proton-conducting membrane with high flatness and density could not be obtained.
[0108] The thickness of the proton-conducting membranes obtained by peeling off the protective sheet was measured. The membrane thicknesses were as follows: Example 1: 7 μm; Example 2: 11 μm; Example 3: 12 μm; Example 4: 18 μm; Example 5: 14 μm; Example 6: 13 μm; Example 7: 111 μm; and Example 8: 138 μm. In Examples 1-6, the membrane thickness was less than 20 μm. In Examples 7 and 8, where the protective sheet was reused, the membrane thickness was less than 150 μm. The membrane thickness of Comparative Examples 1-8 could not be measured.
[0109] In the surface roughness measurement, the root mean square height Sq (μm) was measured in the central part of the surface of the proton conduction membrane obtained by peeling off the protective sheet using an Olympus laser microscope OLS4100.
[0110] The surface roughness of the proton conduction membranes in Examples 1-8 was 1.80-7.72 μm, resulting in proton conduction membranes with high flatness. In contrast, the surface roughness of the proton conduction membranes in Comparative Examples 1-8 was 20.15-101.99 μm, and proton conduction membranes with high flatness could not be obtained.
[0111] The phosphoric acid content of the proton-conducting membrane was determined by neutralization titration with 0.1M sodium hydroxide. The results showed that the phosphoric acid content of the proton-conducting membrane was inversely proportional to the membrane resistance, and the performance of the proton-conducting membrane was related to the amount of phosphoric acid present inside.
[0112] The proton-conducting membrane obtained by peeling off the protective film was cut into rectangles of 20 mm × 30 mm and stirred in 10 mL of pure water for 30 minutes. Two drops of phenolphthalein solution (Fujifilm and Koko Pure Chemical Industries, Ltd., specification: 1.0 w / v%) were added as a pigment, and the mixture was stirred for 5 minutes. A burette was filled with 0.1 M sodium hydroxide, and the solution was added dropwise for neutralization titration. After titration, the proton-conducting membrane was removed, washed with pure water, and then vacuum-dried at 70 °C for 3 hours. Its weight was then determined.
[0113] The phosphoric acid content x of the proton-conducting membrane was calculated using the following formula. Phosphoric acid content x represents the number of phosphate molecules per repeating unit of the resin constituting the proton-conducting membrane.
[0114] [Formula 1]
[0115]
[0116] Among them, V NaOH C represents the volume (l) of sodium hydroxide used in the titration. NaOH W represents the concentration (mol / L) of sodium hydroxide used in the titration. dry M represents the mass (g) of the dried conductive membrane.W The molecular weight (g / mol) of the repeating unit of the polymer in the proton-conducting membrane.
[0117] The phosphoric acid content in Examples 1-8 ranged from 5.50 to 10.85. In Examples 1-8, proton-conducting membranes containing a relatively high amount of phosphoric acid were obtained. In Comparative Examples 1-8, the phosphoric acid content could not be determined.
[0118] Regarding the membrane resistance of the proton conduction membrane, the proton conduction membrane obtained by peeling off the protective sheet was cut into 20 mm square thin slices and used as the electrolyte membrane 130 of the fuel cell unit 100 for measurement. Platinum-supported carbon electrodes of 10 mm square were used as the cathode 110 and anode 120. The two sides of the electrolyte membrane 130 were clamped together with the cathode 110 and anode 120 and pressed together with 0.2 kN, thereby fabricating the fuel cell unit 100.
[0119] AC impedance measurements were performed on fuel cell unit 100, and the membrane resistance of the proton conduction membrane was measured. The measurements were conducted at 120°C under dry nitrogen flow without humidification, in the frequency range of 0.1 Hz to 1 MHz, and under voltage amplitude of 10 mV.
[0120] The membrane resistance of the proton-conducting membranes in Examples 1-8 is 0.04-0.45 Ωμm. 2 The membrane resistance decreases. In Examples 1-8, proton-conducting membranes with excellent proton conductivity can be obtained.
[0121] The membrane resistance of the proton-conducting membranes in Comparative Examples 1-8 could not be measured. In Comparative Examples 1-8, proton-conducting membranes with excellent proton conductivity could not be obtained.
[0122] In the embodiment described above, by using pressure molding to manufacture the proton conduction membrane, the productivity of the proton conduction membrane can be improved. Therefore, it is possible to achieve mass production with a high yield.
[0123] Furthermore, in this embodiment, when the electrolyte resin material dissolved in polyphosphoric acid is thin-filmed by pressure molding, an acidic resin film is used as the protective sheet in contact with the electrolyte resin material. Therefore, moisture in the air can reach the electrolyte resin material through the protective sheet, promoting the hydrolysis and phosphorylation of polyphosphoric acid, and the protective sheet can be easily peeled off from the proton conduction membrane. Thus, even when the proton conduction membrane is manufactured by pressure molding of the electrolyte resin material dissolved in polyphosphoric acid, a proton conduction membrane with high flatness and density can be obtained, thereby achieving a high-quality proton conduction membrane.
[0124] Furthermore, according to this embodiment, by using pressure molding to fabricate the proton conduction membrane, it is easy to achieve a large area of proton conduction membrane and to achieve thin film fabrication. Thus, it is easy to obtain a proton conduction membrane with a thickness of 150 μm or less.
[0125] Furthermore, in the method for manufacturing the proton-conducting membrane according to this embodiment, a hydrolysis step is provided between the pressurization step and the peeling step. In the hydrolysis step, the proton-conducting membrane sandwiched between the protective sheet is exposed to air with a specified humidity for a specified time. This ensures reliable hydrolysis of polyphosphoric acid.
[0126] Furthermore, in the method for manufacturing the proton-conducting membrane of this embodiment, the ambient humidity of the hydrolysis process is increased compared to the pressurization process. Therefore, the hydrolysis of polyphosphoric acid can be suppressed in the pressurization process, the electrolyte resin material can be thinned in its original form as a high-viscosity solution, and the hydrolysis of polyphosphoric acid can be effectively promoted in the hydrolysis process.
[0127] Furthermore, in the proton conduction membrane manufacturing method of this embodiment, the protective sheet can be easily peeled off from the proton conduction membrane during the peeling process. The peeled protective sheet can be directly reused in the next press forming of the proton conduction membrane. Therefore, the productivity of the proton conduction membrane can be improved.
[0128] This disclosure is not limited to the embodiments described above, and various modifications can be made without departing from the spirit of this disclosure, as shown below. Furthermore, the methods disclosed in the above embodiments can be appropriately combined within feasible limits.
[0129] For example, in the above embodiment, the two protective sheets 200 and 201 that contact both sides of the electrolyte resin material 202 are set to acidic resin films, but it is sufficient that the protective sheet in contact with at least one surface of the electrolyte resin material 202 is an acidic resin film. In this case, the protective sheet in contact with the other surface of the electrolyte resin material 202 can be a non-acidic resin film. As a result, moisture in the air can reach the electrolyte resin material 202 through the acidic resin film in contact with one surface of the electrolyte resin material 202, thereby promoting the hydrolysis of polyphosphoric acid.
[0130] This disclosure has been described with reference to embodiments, but it should be understood that this disclosure is not limited to such embodiments or structures. This disclosure also includes various modifications and variations within the same range. Moreover, although various combinations and methods are shown in this disclosure, other combinations and methods that include only one element, more than one element, or less than one element are also included in the scope or spirit of this disclosure.
Claims
1. A method for manufacturing a proton-conducting membrane, comprising: In the pressurization process, the electrolyte resin material is formed into a film by contacting the surface of at least one of the resin film (200, 201) with the electrolyte resin material (202) dissolved in polyphosphoric acid and applying pressure. The hydrolysis process involves phosphorylating the polyphosphoric acid by hydrolyzing it after the pressurization process; and The stripping process involves peeling the resin film from the membrane-like electrolyte resin material after the hydrolysis process to obtain a proton-conducting membrane formed from the membrane-like electrolyte resin material containing phosphoric acid. in, The resin constituting the resin film has acidic substituents.
2. The method for manufacturing a proton-conducting membrane according to claim 1, wherein, The resin constituting the resin film has at least one substituent selected from carboxyl, sulfonyl, hydroxyl, phosphinyl and their derivatives on at least one of the main chain or side chain.
3. The method for manufacturing a proton-conducting membrane according to claim 1 or 2, wherein, In the hydrolysis process, the ambient humidity is increased compared to the pressurization process.
4. The method for manufacturing a proton-conducting membrane according to claim 1 or 2, wherein, The electrolyte resin material is an alkaline resin material having N or NH in the main chain or side chain, or a resin material having at least one substituent selected from sulfonyl, carboxyl, hydroxyl, phosphinyl and their derivatives on at least one of the main chain and side chain.
5. The method for manufacturing a proton-conducting membrane according to claim 4, wherein, The electrolyte resin material is selected from at least one of polybenzimidazole, sulfonated polyimide, perfluorosulfonic acid polymer and their derivatives.
6. The method for manufacturing a proton-conducting membrane according to claim 1 or 2, wherein, The resin film peeled off in the peeling process can be reused in the next pressurization process.
7. The method for manufacturing a proton-conducting membrane according to claim 1 or 2, wherein, The concentration of the electrolyte resin material dissolved in the polyphosphoric acid is in the range of 1 wt% to 20 wt%.
8. The method for manufacturing a proton-conducting membrane according to claim 1 or 2, wherein, The thickness of the proton-conducting membrane is less than 150 μm.
Citation Information
Patent Citations
Karaoke system
JP2021103216A
Proton-conducting polymer film, manufacturing method of the same, and fuel cell using the same
CN101189752A
Proton-conductive polymer electrolyte film having excellent oxidation resistance, and process for production thereof
CN103081031A